Epistemology, Methodology, and Philosophy of Science
III, 484 p.
Keywords: Professor C. G. Hempel (known to a host of admirers and friends as 'Peter' Hempel) is one of the most esteemed and best loved philosophers in the If an Empiricist Saint were not somewhat of a Meinongian Impos world. sible Object, one might describe Peter Hempel as an Empiricist Saint. In deed, he is as admired for his brilliance, intellectual flexibility, and crea tivity as he is for his warmth, kindness, and integrity, and does not the presence of so many wonderful qualities in one human being assume the dimensions of an impossibility? But Peter Hempel is not only possible but actual! One of us (Hilary Putnam) remembers vividly the occasion on which he first witnessed Hempel 'in action'. It was 1950, and Quine had begun to attack the analytic/synthetic distinction (a distinction which Carnap and Reichenbach had made a cornerstone, if not the keystone, of Logical Em piricist philosophy). Hempel, who is as quick to accept any idea that seems to contain real substance and insight as he is to demolish ideas that are empty or confused, was one of the first leading philosophers outside of Quine's immediate circle to join Quine in his attack. Hempel had come to Los Angeles (where Reichenbach taught) on a visit, and a small group consisting of Reichenbach and a few of his graduate students were gath ered together in Reichenbach's home to hear Hempel defend the new posi tion.